Musical life in Slutsk during the years 1733-1760 in the light of archive materials - Bieńkowska, Irena (Interdisciplinary Studies in Musicology, 2018)
This article represents the very first attempt at reconstructing musical life in Slutsk (Pol. Sluck) during the first half of the eighteenth century, and it merely outlines the issues involved. Slutsk was a typical private town - a multicultural centre inhabited by Jews, Orthodox Ruthenians, Lithuanians and Poles of the Protestant and Roman-Catholic faiths. Among the representatives of the Roman-Catholic faith, the Jesuits were the main animators of the town’s cultural and educational life, alongside the court of Prince Hieronim Florian Radziwiłł. A medium-sized music boarding school attached to the Jesuit College in Slutsk existed from around 1713. Musical instruments were purchased for the school quite regularly, often in faraway Koenigsberg. The contacts between the boarding school and the prince’s court were relatively frequent and good, and some school leavers found jobs at the court, chiefly in the garrison or janissary band, and sporadically also in Prince Radziwill’s music ensemble. The court was the main centre of the town’s cultural life. Among its numerous artistic ventures, stage shows seem to have been the most spectacular. For the purposes of such performances, a free-standing theatre was built in the centre of Slutsk at the turn of 1753. This building is worth mentioning because of the rarity of such projects in the Commonwealth of Poland-Lithuania during the 1750s. The repertoire of the Slutsk theatre was initially dominated by commedia dell’arte in German and the occasional dramma per música, but during the second half of the 1750s, one-act ballets began to dominate. Among the instrumental works performed in Slutsk were compositions by Carl Heinrich and Johann Gottlieb Graun, Georg Christoph Wagenseil, and musicians active at the Radziwiłł court (Andreas Wappler, Joseph Kohaut and Johannes Battista Hochbrucker), as well as improvisations by Georg Noelli. The town’s artistic heyday ended with the death of Prince Hieronim Florian Radziwiłł, in 1760, and the dissolution of the Society of Jesus, a decade or so later.